2023
DOI: 10.1037/tra0001152
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive, emotional, and behavioral sequelae of trauma exposure: An integrative approach to examining trauma’s effect.

Abstract: Objective: In this study we tested direct pathways from trauma exposure to trauma symptomatology and risky and self-destructive behavior and indirect pathways through two cognitive and affective mechanisms: 1) world assumptions and 2) emotion dysregulation. Method:A sample of 270 undergraduate students with an average age of 20.02 years participated in the study (204 females and 65 males, and one participant choosing not to disclose). Participants completed self-report measures assessing trauma exposure, traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
6
1
Order By: Relevance
“…Findings are inconsistent with a substantial body of literature suggesting that BCEs have an inverse relationship with psychological symptoms (Hou et al, 2022) and PTSD symptoms (Narayan et al, 2018), and that BCEs buffer against negative outcomes from adversity (Daines et al, 2021). Findings also counter research suggesting that lifetime traumatic events are associated with both PTSD symptom severity and reckless behavior engagement (Contractor et al, 2017; Rizeq & McCann, 2021). There are a few potential explanations for these unexpected findings.…”
Section: Discussioncontrasting
confidence: 80%
“…Findings are inconsistent with a substantial body of literature suggesting that BCEs have an inverse relationship with psychological symptoms (Hou et al, 2022) and PTSD symptoms (Narayan et al, 2018), and that BCEs buffer against negative outcomes from adversity (Daines et al, 2021). Findings also counter research suggesting that lifetime traumatic events are associated with both PTSD symptom severity and reckless behavior engagement (Contractor et al, 2017; Rizeq & McCann, 2021). There are a few potential explanations for these unexpected findings.…”
Section: Discussioncontrasting
confidence: 80%
“…To our knowledge, only one study to date has examined the indirect effect of trauma exposure and risky behavior broadly defined via emotion processing in adults. In a sample of undergraduate students, Rizeq and McCann (2023) found a significant indirect effect of trauma symptoms on past‐month risky behavior through emotion dysregulation, providing further support for the shared etiology of emotional processing and risky behavior. Although these findings suggest that difficulties with emotion regulation mediate the link between trauma exposure and risky behavior, the question of whether heightened emotional reactivity contributes to risky behavior remains.…”
Section: Emotional Reactivity Linking Trauma and Risky Behaviormentioning
confidence: 90%
“…Understanding the role of more specific constructs that contribute to emotion dysregulation may help to increase specificity in etiological models of risky behavior. Further, theoretical models have implicated both emotion regulation and emotional reactivity in the tendency to engage in risky behavior (Nock et al., 2008); however, most research to date has focused on emotion regulation as an intermediate mechanism linking trauma with risky behavior (e.g., Rizeq & McCann, 2023; Weiss et al., 2019). Accordingly, the first aim of this study was to examine whether trauma exposure was indirectly associated with general engagement in past‐month risky behavior via emotional reactivity.…”
Section: Emotional Reactivity Linking Trauma and Risky Behaviormentioning
confidence: 99%
“…Specifically, across studies, adults who reported greater use of these negative ER strategies also reported higher levels of PTSS. Trauma exposure has also been linked with impulsivity and lack of access to adaptive ER strategies (Rizeq & McCann, 2023). Further, ASA has been tied to greater ER difficulties following CSA specifically (Messman-Moore et al, 2013).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Prior work has also focused largely on ER as a broader construct, as opposed to examining the specific dimensions of emotion dysregulation. When studies have investigated different facets of emotion dysregulation, not all of the dimensions were related to trauma exposure or PTSS (e.g., Charak et al, 2018; Rizeq & McCann, 2021). Emotion dysregulation has also been identified as a potentially salient factor in the symptom severity of PTSS (Messman-Moore & Bhuptani, 2017; Pencea et al, 2020).…”
Section: Current Studymentioning
confidence: 99%